G321 Inpatient admission and ED reattendance rates in a cohort of children with IGA vasculitis. (25th October 2020) - Haigh, G; Oni, L; Mulvaney, S
Abstract : Aim: To determine the impact of IgA vasculitis (Henoch Schonlein purpura) on the emergency and acute medical services in a regional paediatric teaching hospital. Method: The case notes of all patients attending Alder Hey Children's Hospital emergency department (ED) and coded as HSP between 1st January 2018 and 31st December 2018 were reviewed retrospectively. Data was collected to establish reasons for admission and reattendance, time between diagnosis and reattendance, and length of inpatient stay on admission. Results: A cohort of 53 patients presented with a new diagnosis of HSP during 2018. 62% were male, 38% female. The mean age was 6 years (range 1 to 13 years). 11 patients (21%) were admitted for symptom management or further investigation. Of these, 4 (36%) were admitted on presentation and 7 (64%) on reattendance. Reasons for admission on presentation included manual blood pressure monitoring (2) and joint pain requiring analgesia (2). All patients were discharged within 24 hours.14 patients (26%) reattended ED with problems relating to HSP. Time between diagnosis and reattendance ranged from 1 day to 123 days (mean = 9 days). The primary reasons for reattendance were pain (10/14;71%), worsening/recurring rash (3/14;21%), and limb swelling (1/14;7%). Of the 10 patients representing with pain 5 complained of joint pain, 2 of abdominal pain, and 3 of both joint and abdominal pain. 50% of the reattending patients required admission (joint pain 5/7; 71%, abdominal pain 2/7; 29%). All patients requiring admission after reattending with joint pain were admitted for less than 24 hours. The 2 patients with abdominal pain alone were diagnosed with intussusception which resolved with non-operative management and had an inpatient stay of 1 and 3 days respectively. Conclusion: The impact of IgA vasculitis in children extends beyond the potential renal involvement. Patient's experience of pain is a significant factor and leads to a high reattendance/admission to hospital rate. Ways to improve supporting patients to recover at home are being investigated as specialist intervention was rarely needed.